Left ventricular mural thrombi with multisystem thrombosis in patients with COVID-19 and myocardial injury: a case series. Issue 6 (26th June 2021) - Garg, Aakash; Hakeem, Hisham; Chennu, Gouthami; Saeed, Qaisra; Vucic, Esad; Kats, Yuliya; Waxman, Sergio
Abstract: Background: Cardiovascular and thromboembolic complications have been reported in patients with Coronavirus disease-2019 (COVID-19)-related severe respiratory distress syndrome. Although myocarditis associated with COVID-19 pneumonia has been described, evidence of left ventricular (LV) mural thrombi with other multisystem events has not been reported. Case summary: We report two cases with severe COVID-19 pneumonia and myocardial injury with large LV thrombi and other multisystem thrombotic events. The first patient represents an unusual case of large LV apical thrombus without concordant regional wall motion abnormality and mildly reduced LV function. A subsequent inferior ST-elevation myocardial infarction (STEMI) was likely related to either an embolic event or in situ coronary thrombosis. We could not ascertain whether the acute right ventricular dysfunction was due to in situ pulmonary thrombosis or inferior STEMI. The catastrophic cerebrovascular accident was likely an embolic phenomenon. Similarly, the second patient demonstrated multiple large pedunculated thrombi occupying one-third of the LV cavity with moderately reduced LV function. A segmental pulmonary embolism was diagnosed on computed tomography chest, confirming multiple territories of in situ thrombosis. Discussion: COVID-19-related inflammatory cytokine release has been linked to activation of coagulation pathways. Marked elevation of ferritin and C-reactive protein levels in both patients were consistent with evidence of a hyperinflammatory state with 'cytokine storm'. Furthermore, the finding of elevated D-dimer levels lends support to the altered coagulation cascade that plausibly explains the multisystem thrombosis observed in our patients. The direct viral endothelial involvement and subsequent endothelial dysfunction may play an important role in the development of thrombosis in different vascular beds, as seen in our patients.